2014
DOI: 10.1111/mcn.12161
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting actualisation of the WHO breastfeeding recommendations in urban poor settings in Kenya

Abstract: Poor breastfeeding practices are widely documented in Kenya, where only a third of children are exclusively breastfed for 6 months and only 2% in urban poor settings.This study aimed to better understand the factors that contribute to poor breastfeeding practices in two urban slums in Nairobi, Kenya. In-depth interviews (IDIs), focus group discussions (FGDs) and key informant interviews (KIIs) were conducted with women of childbearing age, community health workers, village elders and community leaders and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
128
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(147 citation statements)
references
References 54 publications
14
128
0
1
Order By: Relevance
“…A study done by Kimani-Murage et al reported that Household food insecurity negatively influenced exclusive breastfeeding. 21 Respondents in the study indicated that one key reason for not breastfeeding optimally was due to inadequate breast milk, which they associated with lack of adequate food to eat. Maternal level of education has also been reported to influence exclusive breastfeeding by some studies.…”
Section: Socioeconomic Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…A study done by Kimani-Murage et al reported that Household food insecurity negatively influenced exclusive breastfeeding. 21 Respondents in the study indicated that one key reason for not breastfeeding optimally was due to inadequate breast milk, which they associated with lack of adequate food to eat. Maternal level of education has also been reported to influence exclusive breastfeeding by some studies.…”
Section: Socioeconomic Factorsmentioning
confidence: 98%
“…17 Kimani-Murage et al also reported giving water and sugar/glucose and/or salt or commercially prepared mixture of water (gripe water) to protect the baby from stomach problems is a common belief not only among mothers but also among community health or social workers that affects the duration of exclusive breastfeeding. 21 Additionally, in a qualitative study conducted in Korogocho and Viwandani slums, socio-cultural beliefs and practices resulted to suboptimal breastfeeding. Some of the mothers considered colostrum as dirty; others believed that breastfeeding while engaging in extra marital affairs was a bad omen or a curse; fear of the evil eye (malevolent glare that is believed to be a curse associated with witchcraft) when breastfeeding in public while others associated breastfeeding with sagging breasts.…”
Section: Socio Culturalmentioning
confidence: 99%
“…Women in SSA breastfeed their infants for an average of 14 to 19 months, but only 30% to 46% of them practice EBF for the first 6 months postpartum (Bbaale, 2014;Traore et al, 2014;Kimani-Murage et al, 2015). In order to promote infant feeding practices that will significantly reduce MTCT, Prevention of Mother-to-Child Transmission of HIV (PMTCT) programs have to transcend simply informing mothers about feeding practices and documenting their choices.…”
Section: Introductionmentioning
confidence: 99%
“…Kenya Cohort X Kimani-Murage et al (50) 110 Kenya Qualitative Kishore et al (39) 77 India Cross-sectional X Mahmood et al (13) 123 India Cross-sectional X Maman et al (55) 40 DRC Qualitative Maonga et al (23) …”
mentioning
confidence: 99%